Security investigation for LTE-based vehicular networks - Zaw, Kaung Myat (Nanyang Technological University, 2020)
Wireless communication has previously been a basic form of connecting people from one part of the world to another and as the technology advances, short distance communications once again becomes the centre of attention for innovators and researchers. Vehicular communication is one of the wide range applications of wireless communication systems and it provides various services for the users, some of which are traffic efficiency, road safety and infotainment. It is also one of the huge centres of research in Internet of Things (IoT) market and it enables vehicles to communicate to everything (V2X), e.g. vehicle to vehicle, vehicle to infrastructure. In the world of wireless communications, there are many factors to consider when we are implementing or designing a system, which involve reliability, performance, user-friendliness and so on. However, one factor that we sometimes oversee or take for granted the most is the security aspect of building the said system. In terms of security, we need to take into consideration that we are always at a risk of various types of security attacks such as hacking, data manipulation and eavesdropping. From experience and extensive research, security aspects of each and every system are regularly monitored and upgraded and thus, secure data transactions and data confidentiality have been maintained. In traditional vehicular networks, the communication basically involves two methods, firstly between the UE and the end server, secondly, a short distance distributed communication between several UEs. We have found that the security aspects of vehicular communication basically lie within end to end data secrecy and device anonymity, while in the end system aspects, preserving relatively fast authentication and low latency in handshake protocol. In this dissertation project, we reviewed the existing security issues and solutions of LTE-based vehicular networks as part of our literature studies. Afterwards, we suggested the anonymity and reputation-based hybrid authentication scheme that can provide secure and anonymous communication whilst preserving the computation costs or delays in other words, which are evaluated and compared thoroughly.